Agile Governance in Employment Services through the Arek Suroboyo Siap Kerjo (ASSiK) Application at the Department of Industry and Manpower of Surabaya City - Sharifah Shahira; Rosyidatuzzahro Anisykurlillah (Publik : (Jurnal Ilmu Administrasi), 2025)
The need for adaptive, efficient, and technology-based public services is becoming increasingly urgent amid rapid environmental changes, particularly in the employment sector. This condition encourages bureaucracies to respond adaptively, one of which is through the application of agile governance. The Covid-19 pandemic prompted the Department of Industry and Manpower of Surabaya City to shift its conventional job fair services to a digital system through the launch of the Arek Suroboyo Siap Kerjo (ASSiK) application an innovation based on information technology that connects job seekers and companies online. This study aims to analyze the implementation of agile governance principles in employment services through ASSiK at the Department of Industry and Manpower of Surabaya City. The principles include: value proposition and agility shift, leadership readiness for change, citizen-centric approach, and human resource investment. This research uses a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings indicate that the implementation of agile governance has been fairly optimal, especially in the aspects of value proposition and human resource investment. However, challenges remain in leadership readiness for change, particularly due to limited staffing and the absence of Standard Operating Procedures (SOP) for ASSiK usage. Additionally, the citizen-centric approach has not been fully realized due to the lack of collaboration with stakeholders in service standard formulation and the limited reach of socialization efforts. The study recommends adding ASSiK management personnel, drafting SOPs, strengthening stakeholder collaboration, and enhancing the effectiveness of outreach to reach more job seekers.